Dialog and Teenagers’ Second Language Speaking Fluency: Critical Pedagogy Contribution to Second Language Acquisition - Diki Rosadi; Lusiana Suciati Dewi (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aims to analyze the role of dialogue as a central principle of Critical Pedagogy and to examine its contribution to adolescents’ fluency in learning English as a Foreign Language. Drawing on Freire’s dialogic educational concept and Second Language Acquisition theory, this study explores how dialogic interaction supports the development of students’ speaking skills. The study employed a qualitative case study design involving one English teacher and three eleventh-grade students at a high school in Indonesia. Data were collected through classroom observations and semi-structured interviews. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), which includes data condensation, data presentation, and conclusion drawing. The results show that dialogue is implemented through several activities such as open-ended questions, prompts, group discussions, classroom interaction routines, and student involvement in learning decision-making. These dialogic practices create a democratic and supportive learning environment, encouraging students to be more active in expressing their opinions. Furthermore, dialogue contributes positively to students’ fluency through increased self-confidence, decreased speaking anxiety, the emergence of more spontaneous language production, and the negotiation of meaning during interactions. The research findings also indicate that dialogic activities support the second language acquisition process by providing comprehensible input, meaningful output, and meaningful social interactions. This study concludes that dialogue not only functions as a pedagogical strategy but also as an effective mechanism for improving speaking fluency and supporting second language acquisition in adolescent EFL learners.